2008
DOI: 10.1143/jjap.47.7486
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Sensing Properties of SrTiO3 Thin Films

Abstract: The oxygen sensing properties of SrTiO 3 -based thin films have been investigated at room temperature. First, nondoped SrTiO 3 was investigated. Although such a material is highly sensitive, its electrical resistance was too high and not feasible for practical use. Donor (Nb 5þ ) could lower the resistance of SrTiO 3 ; however, the sensitivity was lost. UV-light irradiation or t 2 -type acceptor (Cr 3þ ) doping could lower the resistance and yet maintain the sensitivity. In contrast to t 2 -type acceptor dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 17 publications
1
38
2
2
Order By: Relevance
“…Being one of the most typical materials, SrTiO 3 (STO) has been extensively investigated as oxygen-sensing materials [1,2] and superconducting substrate materials [3] owing to its unique properties. In addition, STO as a stable n-type semiconductor material has extensive applications in photoelectrochemical (PEC) water splitting [4] and photocatalytic degradation of organic compounds [5].…”
Section: Introductionmentioning
confidence: 99%
“…Being one of the most typical materials, SrTiO 3 (STO) has been extensively investigated as oxygen-sensing materials [1,2] and superconducting substrate materials [3] owing to its unique properties. In addition, STO as a stable n-type semiconductor material has extensive applications in photoelectrochemical (PEC) water splitting [4] and photocatalytic degradation of organic compounds [5].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed measurement conditions were described in our previous paper. 17) In this work, the resistance of the films was measured at room temperature both in air and in He atmosphere, then the sensitivity was calculated as the difference of resistance (R(in air)-R(in He)). The crystal structure of the films was measured using an X-ray diffraction (Rint 2200, Rigaku Co.).…”
Section: Methodsmentioning
confidence: 99%
“…4, 5 and 6, it can be mentioned that the sensitivity for an oxygen gas is closely related to the leakage current, and to improve the oxygen sensitivity, it is important to suppress the leakage current. Hara et al 17) examined the effect of Nb-doping into a SrTiO3 thin film on the oxygen sensitivity, and they found that the sensitivity decreases by a carrier doping. The result of the Dy-doping agrees well with the report.…”
Section: Jcs-japanmentioning
confidence: 99%
See 2 more Smart Citations